2012
DOI: 10.1540/jsmr.48.125
|View full text |Cite
|
Sign up to set email alerts
|

Combined pH-impedance monitoring and high-resolution manometry of Japanese patients treated with proton-pump inhibitors for persistent symptoms of non-erosive reflux disease

Abstract: Background: Data on acid and non-acid reflux patterns and esophageal function in Japanese patients with non-erosive reflux disease (NERD) are limited. The aim of this study was to use combined multichannel intraluminal impedance pH monitoring (MII-pH) and high-resolution manometry (HRM) to investigate the characteristics of Japanese patients who were treated with a "double-dose" (20 mg) of rabeprazol (a proton-pump inhibitor; PPI) for persistent symptoms of NERD. Methods: Twenty-five patients who complained of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…In Japan, persistent symptoms despite taking standard doses of PPI were regarded as PPI-resistant NERD in some reports [5,6], and those despite taking double doses of PPI were regarded as PPI-resistant NERD in others [17,18], but the latter are defined as PPI-resistant NERD in many reports from Western countries [13,15,19,20,21]. To rule out acid reflux as much as possible, taking a double dose of PPI should be tried once, and we defined these patients with persistent symptoms as PPI-resistant NERD.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, persistent symptoms despite taking standard doses of PPI were regarded as PPI-resistant NERD in some reports [5,6], and those despite taking double doses of PPI were regarded as PPI-resistant NERD in others [17,18], but the latter are defined as PPI-resistant NERD in many reports from Western countries [13,15,19,20,21]. To rule out acid reflux as much as possible, taking a double dose of PPI should be tried once, and we defined these patients with persistent symptoms as PPI-resistant NERD.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of proximal reflux remains poorly understood. We previously reported that, in patients with GERD, primary peristalsis pressure and a successful peristalsis ratio at the proximal esophagus were significantly lower than in healthy volunteers; this proximal esophageal dysfunction might allow for the entry of refluxate into the proximal esophagus [29]. In this study, all asymptomatic subjects had normal esophageal peristalsis; therefore, acotiamide might not be able to decrease proximal reflux events significantly.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies had revealed that RGERD was more strongly related with weakly acid reflux and alkaline reflux than acid reflux. 6,24,38,39 Furthermore, long term usage of PPI might reduce the detective acid reflux episodes difference between the 2 groups. In addition, only 48 patients were enrolled in our study, and the small sample size might be related with the results.…”
Section: Discussionmentioning
confidence: 99%